The Influence of Leadership and Work Environment on Lecturer Performance Through Job Satisfaction - Ifa Khoiria Ningrum; Nur Mahmudah; Mohd Shahid Azim bin Mohd Saufi (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Globalization in the 5.0 era advances technology in communication and information, impacting human resources, services, and education. Lecturers, crucial for educational progress and higher education quality, engage in teaching, research, community service, and other key tasks. Quality education requires universities to develop standards for lecturer performance, influenced by leadership, work environment, and job satisfaction. Lecturer performance reflects the competence and progress of higher education institutions. Poor understanding of competence in lecturer performance lowers lecturers' societal standing, reducing education quality. So comprehensive and efficient modeling with analysis is needed Partial Least Square (PLS). The purpose of this research is to determine the influence of leadership and work environment on lecturer performance through job satisfaction. This research was conducted at the Nahdlatul Ulama Sunan Giri Bojonegoro University with respondents 58 permanent lecturers who had academic positions as expert assistants and lecturers using Partial Least Square (PLS). The research results show that the work environment has a significant effect on job satisfaction and lecturer performance. Other variables not contained in the research model, explain leadership, work environment, and job satisfaction by 34.2% such as work motivation, competency, organizational culture, and commitment variables.